Harnessing AI-Chat GPT (Generative Pretrained Transformer) to engage youths and women in climate-smart, sustainable livestock farming - Zeleke, Muluken; Wamatu, Jane (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
To assess the potential of AI-Chat GPT in providing information and provoking climate-smart sustainable livestock farming to youths and women.